Community-acquired lobar pneumonia in children in the era of universal 7-valent pneumococcal vaccination: a review of clinical presentations and antimicrobial treatment from a Canadian pediatric hospital - Rowan-Legg Anne; Barrowman Nicholas; Shenouda Nazih; Koujok Khaldoun; Le Saux Nicole (BMC, 2012)
Abstract Background Community-acquired pneumonia (CAP) is a common cause of pediatric admission to hospital. The objectives of this study were twofold: 1) to describe the clinical characteristics of CAP in children admitted to a tertiary care pediatric hospital in the pneumococcal vaccination era and, 2) to examine the antimicrobial selection in hospital and on discharge. Methods A retrospective review of healthy immunocompetent children admitted to a tertiary pediatric hospital from January 2007 to December 2008 with clinical features consistent with pneumonia and a radiographically-confirmed consolidation was performed. Clinical, microbiological and antimicrobial data were collected. Results One hundred and thirty-five hospitalized children with pneumonia were evaluated. Mean age at admission was 4.8 years (range 0-17 years). Two thirds of patients had been seen by a physician in the 24 hours prior to presentation; 56 (41.5%) were on antimicrobials at admission. 52 (38.5%) of patients developed an effusion, and 22/52 (42.3%) had pleural fluid sampled. Of 117 children who had specimens (blood/pleural fluid) cultured, 9 (7.7%) had pathogens identified (7 Streptococcus pneumoniae, 1 Group A Streptococcus, and 1 Rhodococcus). 55% of patients received 2 or more antimicrobials in hospital. Cephalosporins were given to 130 patients (96.1%) in hospital. Only 21/126 patients (16.7%) were discharged on amoxicillin. The median length of stay was 3 days (IQR 2-4) for those without effusion and 9 (IQR 5-13) for those with effusion. No deaths were related to pneumonia. Conclusions This study provides comprehensive data on the clinical characteristics of hospitalized children with CAP in the pneumococcal 7-valent vaccine era. Empiric antimicrobial choice at our institution is variable, highlighting a need for heightened antimicrobial stewardship.